2021
DOI: 10.2106/jbjs.oa.20.00067
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers for Diagnosing Periprosthetic Joint Infection from Synovial Fluid and Serum

Abstract: Background: Synovial fluid bacterial culture is the cornerstone of confirmation or exclusion of periprosthetic joint infection (PJI). The aim of this study was to assess synovial fluid and serum biomarker patterns of patients with total joint arthroplasty (TJA), and the association of these patterns with PJI. Methods: Synovial fluid and serum samples were collected from 35 patients who were admitted to the Arthroplasty Unit of the Department of Orthopae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Interestingly, while each of these proteins is important for chemoattraction and inflammatory response of macrophages and neutrophils 66 , 84 86 , CCL20, as mentioned previously, and IL8 were present in higher levels in PJI compared to NIAF, while MCP-1 and CCL3 were present in lower levels in PJI compared to NIAF. While some identified proteins, including IL6, IL8, IL17A, IFNγ, and TWEAK have been found in synovial fluid or serum of subjects with PJI 22 , 27 , 30 , others, such as CCL20, OSM, EN-RAGE, and CXCL6, are more novel. Further investigation into the diagnostic power of these candidate biomarkers and potential for targeted treatment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while each of these proteins is important for chemoattraction and inflammatory response of macrophages and neutrophils 66 , 84 86 , CCL20, as mentioned previously, and IL8 were present in higher levels in PJI compared to NIAF, while MCP-1 and CCL3 were present in lower levels in PJI compared to NIAF. While some identified proteins, including IL6, IL8, IL17A, IFNγ, and TWEAK have been found in synovial fluid or serum of subjects with PJI 22 , 27 , 30 , others, such as CCL20, OSM, EN-RAGE, and CXCL6, are more novel. Further investigation into the diagnostic power of these candidate biomarkers and potential for targeted treatment is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A number of specific biomarkers showed promise in the diagnosis of PJI, including synovial soluble tumor necrosis factor receptor 2 (sTNF-R2) 33 , synovial fluid interleukin-1 beta (IL-1β) (especially in combination with the polymorphonuclear [PMN] percentage) 34 , and calprotectin (of note, calprotectin did not reliably differentiate PJI from rheumatoid arthritis in this study) 35 . In 1 study, a calprotectin point-of-care test showed high sensitivity and specificity (>95%) in the diagnosis of PJI after TKA 36 .…”
Section: Diagnosismentioning
confidence: 83%
“…Biomarkers from blood and synovial fluid provide diagnose PJI with material evidence. For a host of researchers, much attention has been paid to discovering a novel and promising biomarker that has the potential to be a biomarker for diagnostic criteria compared with current ones [ 33 ]. Many researches show that synovial biomarkers are more useful than those from blood at accuracy diagnosis of PJI, such as α-defensin, interleukin-6, interleukin-1β, leukocyte esterase, and interleukin-17 [ 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%